Low-Density Lipoprotein Cholesterol Lowering With Evolocumab and Outcomes in Patients With Peripheral Artery Disease: Insights From the FOURIER Trial (Further Cardiovascular Outcomes Research With PCSK9 Inhibition in Subjects With Elevated Risk). Issue 4 (23rd January 2018) - Bonaca, Marc P.; Nault, Patrice; Giugliano, Robert P.; Keech, Anthony C.; Pineda, Armando Lira; Kanevsky, Estella; Kuder, Julia; Murphy, Sabina A.; Jukema, J. Wouter; Lewis, Basil S.; Tokgozoglu, Lale; Somaratne, Ransi; et al.
Abstract : Background: The PCSK9 (proprotein convertase subtilisin/kexin type 9) inhibitor evolocumab reduced low-density lipoprotein cholesterol and cardiovascular events in the FOURIER trial (Further Cardiovascular Outcomes Research With PCSK9 Inhibition in Subjects With Elevated Risk). We investigated the efficacy and safety of evolocumab in patients with peripheral artery disease (PAD) as well as the effect on major adverse limb events. Methods: FOURIER was a randomized trial of evolocumab versus placebo in 27 564 patients with atherosclerotic disease on statin therapy followed for a median of 2.2 years. Patients were identified as having PAD at baseline if they had intermittent claudication and an ankle brachial index of <0.85, or if they had a prior peripheral vascular procedure. The primary end point was a composite of cardiovascular death, myocardial infarction, stroke, hospital admission for unstable angina, or coronary revascularization. The key secondary end point was a composite of cardiovascular death, myocardial infarction, or stroke. An additional outcome of interest was major adverse limb events defined as acute limb ischemia, major amputation, or urgent peripheral revascularization for ischemia. Results: Three thousand six hundred forty-two patients (13.2%) had PAD (1505 with no prior myocardial infarction or stroke). Evolocumab significantly reduced the primary end point consistently in patients with PAD (hazard ratio [HR] 0.79; 95% confidence interval [CI], 0.66–0.94; P =0.0098) and without PAD (HR 0.86; 95% CI, 0.80–0.93; P =0.0003; P interaction =0.40). For the key secondary end point, the HRs were 0.73 (0.59–0.91; P =0.0040) for those with PAD and 0.81 (0.73–0.90; P <0.0001) for those without PAD ( P interaction =0.41). Because of their higher risk, patients with PAD had larger absolute risk reductions for the primary end point (3.5% with PAD, 1.6% without PAD) and the key secondary end point (3.5% with PAD, 1.4% without PAD). Evolocumab reduced the risk of major adverse limb events in all patients (HR, 0.58; 95% CI, 0.38–0.88; P =0.0093) with consistent effects in those with and without known PAD. There was a consistent relationship between lower achieved low-density lipoprotein cholesterol and lower risk of limb events ( P =0.026 for the beta coefficient) that extended down to <10 mg/dL. Conclusions: Patients with PAD are at high risk of cardiovascular events, and PCSK9 inhibition with evolocumab significantly reduced that risk with large absolute risk reductions. Moreover, lowering of low-density lipoprotein cholesterol with evolocumab reduced the risk of major adverse limb events. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT01764633. Abstract : Supplemental Digital Content is available in the text.